2016
DOI: 10.1515/bog-2016-0025
|View full text |Cite
|
Sign up to set email alerts
|

Community-based tourism in practice: evidence from three coastal communities in Bohuslän, Sweden

Abstract: Abstract. Local involvement in tourism development is defined as a key issue for sustainable tourism, however it is often questioned and less seldom implemented in reality. Reasons behind this condition are lack of knowledge and practical experience on community-based tourism as a bottom-up approach. In this paper it is argued that local involvement in tourism development is both a democratic right and a strategic destination management tool. The paper scrutinizes a process of collaboration and local participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 20 publications
0
16
1
1
Order By: Relevance
“…Besides, creating a sense of belonging has been hired for the protection of the natural and cultural heritage by policymakers in these countries. In addition, the results of the current study are not in line with the results of the studies of Strzelecka (2012), and Lindström and Larson (2016) in Europe, emphasizing the importance of collaborative development and economic well-being improvement through strengthening the interactions of local tourism stakeholders and provide supportive services to promote the creativity and innovation of local tourism stakeholders in the villages of the route and the destination of tourism. Furthermore, the findings from Lee (2013) and Zou et al (2017) in the East Asian countries indicated a change in policies for participating local tourism stakeholders and establishing social justice in tourism activities through the method facilitators and the process of empowerment.…”
Section: Dependent Variable B: Promoting Sustainable Rural Developmencontrasting
confidence: 99%
“…Besides, creating a sense of belonging has been hired for the protection of the natural and cultural heritage by policymakers in these countries. In addition, the results of the current study are not in line with the results of the studies of Strzelecka (2012), and Lindström and Larson (2016) in Europe, emphasizing the importance of collaborative development and economic well-being improvement through strengthening the interactions of local tourism stakeholders and provide supportive services to promote the creativity and innovation of local tourism stakeholders in the villages of the route and the destination of tourism. Furthermore, the findings from Lee (2013) and Zou et al (2017) in the East Asian countries indicated a change in policies for participating local tourism stakeholders and establishing social justice in tourism activities through the method facilitators and the process of empowerment.…”
Section: Dependent Variable B: Promoting Sustainable Rural Developmencontrasting
confidence: 99%
“…Participation as an indicator of community organization, is significantly important to be evaluated, as it is one of the principles of CBT (Faxina & Freitas, 2020;Lindström & Larson, 2016;López-Guzmán et al, 2011;Lucchetti & Font, 2013). Through it, it is possible to mitigate conflicts of interest inherent to the neoliberal free market model, and, when guided by ethical values, it determines the philosophy of sustainable tourism planning and contribute to the construction of sustainable locations, especially with regard to continuous assessment developed actions (Burns, 2004;Gunn & Var, 2002;Hall, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…In its basic sense CBT follows the holistic approach that views tourism as an economic driver which enables each community member to have an equal access to the improved quality of life (Harwood 2010). According to Lindström and Larson (2016) there are four basic phases in every CBT project: step 1, formation of a representative project group and negotiation of community-based approach; step 2, consulting local stakeholders and employing a mixed-methods approach; step 3, elaborating results with local stakeholders; step 4, increased community collaboration. As the figure 2 shows, an engagement (cooperative) platform (founded by experts and strategic partners) should enable individuals and enterprises to co-create products, services and experiences that will provide new values with simultaneous reduction of risk and costs.…”
Section: How To Develop a Holistic Products And Services?mentioning
confidence: 99%